Procalcitonin to guide taking blood cultures in the intensive care unit; a cluster-randomized controlled trial. (February 2017) - van der Geest, P.J.; Mohseni, M.; Nieboer, D.; Duran, S.; Groeneveld, A.B.J.
Abstract: Objectives: We aimed to study the safety and efficacy of procalcitonin in guiding blood cultures taking in critically ill patients with suspected infection. Methods: We performed a cluster-randomized, multi-centre, single-blinded, cross-over trial. Patients suspected of infection in whom taking blood for culture was indicated were included. The participating intensive care units were stratified and randomized by treatment regimen into a control group and a procalcitonin-guided group. All patients included in this trial followed the regimen that was allocated to the intensive care unit for that period. In both groups, blood was drawn at the same moment for a procalcitonin measurement and blood cultures. In the procalcitonin-guided group, blood cultures were sent to the department of medical microbiology when the procalcitonin was >0.25 ng/mL. The main outcome was safety, expressed as mortality at day 28 and day 90. Results: The control group included 288 patients and the procalcitonin-guided group included 276 patients. The 28- and 90-day mortality rates in the procalcitonin-guided group were 29% (80/276) and 38% (105/276), respectively. The mortality rates in the control group were 32% (92/288) at day 28 and 40% (115/288) at day 90. The intention-to-treat analysis showed hazard ratios of 0.85 (95% CI 0.62–1.17) and 0.89 (95% CI 0.67–1.17) for 28-day and 90-day mortality, respectively. The results were deemed non-inferior because the upper limit of the 95% CI was below the margin of 1.20. Conclusion: Applying procalcitonin to guide blood cultures in critically ill patients with suspected infection seems to be safe, but the benefits may be limited. Trial registration: ClinicalTrials.gov identifier: IDNCT01847079 . Registered on 24 April 2013, retrospectively registered.